In Pursuit of Empowering the Culturally Fragile - an Emic Approach and Indigenous Methodology in a European Research Context - Justyna Pilarska (Nicolaus Copernicus University in Toruń, 2019)
This article was inspired by my long-standing experience in conducting field research in the culturally diverse environment of Bosnia-Herzegovina. It contributes to the better understanding of emic research, reviewing indigenous strategies and the importance of increasing the researcher's cultural sensitivity and awareness of the cultural peculiarities they wish to investigate, through the adaptation of qualitative methods. Moreover, the article adds to the ways in which research projects are designed, acknowledging the equal status of the participants (neither the respondents nor "the researched") who can (and should) be approached ethically and with full recognition of their status as the co-producers of knowledge. Such an outlook towards one's own project can provide an important input to the emancipation and recognition of culturally fragile groups, such as ethnic or religious minorities, refugees, groups subject to social exclusion, etc. The lessons I have learned in the course of almost 17-years experience of doing field research in a multicultural setting (Bosnia-Herzegovina), also including some failures in this regard, inspired me to propose this paper as a starting point of a broader debate on conducting socially and ethically responsible field research in a multicultural society, or amongst culturally diverse groups.